Evaluation of the i-STAT Point-of-Care Analyzer in Critically Ill Adult Patients - Steinfelder-Visscher, Jacoline (J Extra Corpor Technol, 2008)
Point-of-care analyzers may benefit therapeutic decision making by reducing turn-around-time for samples. This is especially true when biochemical parameters exceed the clinical reference range, in which acute and effective treatment is essential. We therefore evaluated the analytical performance of the i-STAT point-of-care analyzer in two critically ill adult patient populations. During a 3-month period, 48 blood samples from patients undergoing cardiac surgery with cardiopulmonary bypass (CPB) and 42 blood samples from non-cardiac patients who needed intensive care treatment were analyzed on both the i-STAT analyzer (CPB and non-CPB mode, respectively) and our laboratory analyzers (RapidLab 865/Sysmex XE-2100 instrument). The agreement analysis for quantitative data was used to compare i-STAT to RapidLab for blood gas/electrolytes and for hematocrit with the Sysmex instrument. Point-of-care electrolytes and blood gases had constant deviation, except for pH, pO(2), and hematocrit. A clear linear trend in deviation of i-STAT from RapidLab was noticed for pH during CPB (r = 0.32, p = .03) and for pO(2) > 10 kPa during CPB (r = −0.59, p < .0001 when 10 < pO(2) <30 kPa) and in the intensive care unit (r = −0.61, p < .001 when 10 < pO(2) <30 kPa). In the normal pO(2) range (10.6 < pO(2) <13.3 kPa), the performance of the i-STAT was comparable to the RapidLab. In contrast to hematocrit measured during CPB, hematocrit using the non-CPB mode in the non-cardiac intensive care population showed an underestimation up to 2.2% (p < .0001) in the hematocrit range below 25% (n = 11) using the i-STAT. The i-STAT analyzer is suitable for point-of-care testing of electrolytes and blood gases in critically ill patients, except for high pO(2). However, the discrepancy in hematocrit bias shows that accuracy established in one patient population cannot be automatically extrapolated to other patient populations, thus stressing the need for separate evaluation.